Gross and Histopathology of Goats Feeding on Opuntia stricta in Laikipia County, Kenya - Jackson M. Ncebere; Paul G. Mbuthia; Robert M. Waruiru; Peter K. Gathumbi (Veterinary Medicine International)
Various plant species such as Opuntia stricta have developed defensive measures, namely, spines, thorns, and other sharp pointed structures to protect themselves from herbivores and other animals feeding on them. Opuntia stricta has invaded the northern part of Laikipia County, Kenya, and its fruits are protected by small spines called glochids. This study determined the pathology in goats feeding on this plant in Laikipia County. Eighteen goats that had eaten the plant and six others that were raised in a ranch without O. stricta were purchased for the study. All study animals were clinically examined for lesions and euthanized for necropsy examination. Clinically, goats affected by O. stricta had poor body condition, wounds on various body parts, and diarrhea. Variable numbers of O. stricta spines occurred externally on the skin throughout the body and elicited pain, swelling, and ulcerative wounds on affected parts. Internal lesions were observed in subcutaneous tissues (100%), together with stomatitis, cheilitis, gingivitis, glossitis, abomasitis (100%), rumen, reticulum, omasum thinning and loss of papillae (72.2%), esophagitis, and duodenitis (5.6%). Carcasses had gelatinous fat and muscular atrophy. Other gross lesions were generalized viscera atrophy, edema, subcutaneous emphysema, lymphadenopathy, abscesses, ascites, hydrothorax, and hydropericardium. The abomasum wall and its mucosal folds were swollen with edema, haemorrhages, and scattered foci of abscesses. Histopathology confirmed the main lesions in all affected goats were foreign-body granulomas which were located in all organs with gross lesions. Goats from O. stricta-free ranches had no spines or lesions. The pathological effects caused by O. stricta resulted in emaciated goats due to pain, inability to masticate and assimilate food, and stress, resulting in poor carcass and organs quality and possible condemnation and death. This could affect the socioeconomics and livelihoods of communities in the study area, and therefore, the spread of this plant needs to be controlled.